A Comprehensive Review of Environmental and Economic Impacts of Autonomous Vehicles - Uzzaman, Asif; Muhammad, Waseem (Control Systems and Optimization Letters, 2024)
The development of autonomous vehicles (AVs) holds great potential for revolutionary improvements in several fields, most notably the economic and environmental domains. This paper analyzes the two-pronged effects of AVs, showing both the advantages and disadvantages that may arise. With their enhanced fuel efficiency, integrated electric vehicle technology, and driving behaviors, autonomous vehicles (AVs) have the potential to drastically reduce emissions and have a positive environmental impact. Lower carbon footprints could also be achieved by improved urban design and the possibility of less traffic congestion. In terms of the economy, AVs present chances for new transportation service business models, lower accident-related costs, and cost reductions in logistics. Nevertheless, there are drawbacks to these developments as well, such as high upfront costs, the possibility of employment displacement in the driving industry, and the requirement for strong regulatory frameworks to guarantee security and safety. It is anticipated that autonomous vehicles will improve lane management, acceleration, and deceleration, which could result in less gasoline being used. In a place like California where traffic congestion is a well-known issue, this is especially pertinent. When paired with electric cars (EVs), autonomous vehicles (AVs) have the potential to significantly lower greenhouse gas (GHG) emissions, supporting California aggressive climate targets, which include becoming carbon neutral by 2045. To maximize the positive effects of AVs while minimizing their negative effects, this review summarizes the most recent studies, offering a fair assessment of their implications. It also identifies important topics for further research.